The Effectiveness Of Character Education Based On Islamic Values - Muhammad Azam Purba; Indra Prasetia; Amini Amini (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
Character education based on Islamic values is an important necessity inresponding to the challenge of moral degradation among elementary school students. Elementary schools, as the foundation of formal education, have a strategic role in instilling moral, spiritual, and social values in an integrated manner. This study aims to analyze the implementation and effectiveness of Islamic values-based character education at SD Negeri No. 107463 Paya Pasir. The study uses a qualitative approach with a case study design. Data collection techniques include observation, in-depth interviews with the principal and teachers, and documentation studies. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing with source triangulation to ensure data validity. The results showed that character education based on Islamic values was implemented in an integrated manner through classroom learning, habit-forming activities, school culture, and extracurricular programs. This implementation is quite effective in shaping students' character, especially in terms of religiosity, honesty, discipline, responsibility, social awareness, leadership, and ethical decision-making skills in everyday life. The success of the program is supported by teachers' exemplary behavior, consistent religious habits, reinforcement of rules and behavior monitoring, and a conducive school climate. However, the study also found challenges in the form of differences in the family backgrounds of students, which affected the consistency of character behavior. These findings confirm that Islamic values-based character education in public elementary schools has strong potential to shape ethical and responsible behavior, provided that there is continuous synergy between schools and families.